Pressure injury prevention in the operating unit of a Swiss university hospital: a best practice implementation project. Issue 1 (14th March 2023) - Perrenoud, Beatrice; Maravic, Philippe; Delpy, Pierre
ABSTRACT: Objectives: The aim of this project was to promote best practice in pressure injury prevention for patients during the intraoperative period in the main operating unit of a Swiss tertiary hospital, through improving risk assessment, safe positioning and documentation. Introduction: Pressure injury is a common and serious complication of surgery patients. Despite pressure injuries being mostly preventable, they are not a top priority of operating room professionals. Methods: A baseline audit was conducted using the JBI Practical Application of Clinical Evidence System, applying nine evidence-based criteria. The audit was followed by the implementation of multiple strategies to promote best practice in pressure injury prevention. A follow-up audit was conducted to determine the compliance with best practice recommendations. Results: The baseline audit indicated poor compliance with evidence-based practice in most audited criteria. The project team identified barriers to best practice and strategies implemented to improve practice, including tailored education, direct support in each surgery specialty, assignment of responsibilities regarding pressure injury prevention measures among the multidisciplinary team members and multiple channels of communication. Improvements in practice were observed in eight of nine criteria in the follow-up audit. Conclusion: The project demonstrated important positive changes in pressure injury prevention during the intraoperative period, despite a sharp slowdown in its implementation process. Continuing education for nursing and nonnursing practitioners has been systematized. Follow-up audits will need to be conducted in the future to maintain pressure injury prevention processes, and contribute to safety of care in adult patients during the perioperative period.